Geriatric mental health disaster and emergency preparedness (Springer Pub. Co., 2010)
A primer for disaster and emergency preparedness and evidence-based care practices in geriatric mental health / John A. Toner and Othmane Alami -- Older persons in disasters and emergencies : the overlapping mental and physical health issues / Neil Hall -- The geriatric emergency preparedness and response (GEPR) collaborative : a successful and productive network / Judith L. Howe -- Coordinating services : state and local networks and resources / William Grant and Douglas M. Sanders -- National and cross-national models of geriatric disaster preparedness : the Canadian context / Trish Dryden and Lynda Atack -- Supervision and facilitated reflective practice as central to disaster preparedness services to the older adult : a national and cross-national model / Philippa Sully, Malcolm T. Wandrag, and Jenny Riddell -- Making the community plan : a public health perspective / Andrea Villanti -- Self help tools for older persons and their caregivers / Nina Tumosa -- Volunteers : who are they and what are their roles? / Nora O'Brien-Suric